1189. Correlation of BK polyomavirus (BKPyV)-specific Immunity and BKPyV Viruria within 6 months after Kidney Transplantation: A Prospective Cohort Study. (31st December 2020) - Siripoon, Tanaya; Kantachuvesiri, Surasak; Apiwattanakul, Nopporn; Bruminhent, Jackrapong
Abstract: Background: Since viral-specific immunity has been shown to be correlated with viral containment in solid organ transplant recipients, we investigated an association of BK polyomavirus (BKPyV)-specific immunity and BKPyV viruria in kidney transplant (KT) recipients. Methods: A prospective cohort study of all adult KT recipients between January and August 2019 was conducted. High-level BKPyV viruria was defined as the presence of BKPyV viral load in urine > 7log10 copies/mL. BKPyV-specific immunity was measured by an intracellular cytokine assay measuring the percentage of IFN-γ-producing CD4 +, CD8 +, NK, and NKT cells, after stimulation with large-T antigen (LT) and viral capsid protein 1 (VP1). The incidence of high-level BKPyV viruria within 6 months after KT was estimated by the Kaplan-Meier method. Clinical and immunological factors were analyzed using Cox proportional hazard model. BKPyV-specific immune responses prior to and at 1 month after KT were compared using a mixed-linear regression test. Results: Among 90 evaluable patients, 37% were female with a mean age + SD of 42 + 12 years. Sixty-four and 68 % received deceased-donor KT and induction immunosuppressive therapy, respectively. The cumulative incidence of BKPyV viruria within 6 months was 20%. In multivariate analysis, pre-transplant factors which were independently associated with BKPyV viruria were panel-reactive antibody of 11-50 % (HR 13.35; 95%CI, 1.926-92.590; P = 0.009), %natural killer (NK) cells (HR 1.26; 95%CI, 1.077-1.469; P = 0.004), and %VP1-specific NK cells (HR 1.25; 95%CI, 1.088-1.433; P = 0.002). Among those with BKPyV viruria, the mean %NK, %VP1-specific NK cells and %NKT cells at 1-month post-KT were significantly increased over time as compared to pre-KT (coefficient: 1.202; 95%CI, 0.033-2.371; P = 0.04), (coefficient: 2.602; 95%CI, 1.083-4.121; P = 0.001), and (coefficient: 0.199; 95%CI, 0.051-0.348; P = 0.008), respectively. Conclusion: A presence and increasing proportion of NK, VP1-specific NK and NKT cells were observed among KT recipients who developed early and clinically significant BKPyV viruria in our cohort. Quantification of BKPyV-specific NK and NKT cell immune monitoring could potentially stratify those at risk of BKPyV viruria among KT recipients. Disclosures: All Authors : No reported disclosures